Utilization of waste cooking oil as a sustainable product to improve the physical and rheological properties of asphalt binder: a review - Eldeek, Mahmoud Ibrahim; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin (Springer Cham, 2022)
Yearly, vast numbers of new roads are constituted and existing ones are restored on a regular basis. The usage of recycled asphalt pavement (RAP) aids to minimise dependency on natural resources. Hence, organic regenerator such as waste cooking oil (WCO), have recently been proposed as a sustainable commodity to enhance the recycling of aged asphalt. This paper summarised the potential of WCO being utilized as a renewable commodity in order to boost asphalt binder recycling. Physical properties tests for instance ductility test, softening point test, penetration test, flash & fire point test and specific gravity tests; are commonly adopted alongside test for rheological properties for example dynamic shear rheometer (DSR), Multiple Stress Creep Recovery (MSCR) tests linear amplitude sweep (LAS) and have all been adopted to enhance the binder properties. Generally, this paper offers an abbreviation of the favourable and unfavourable effects of WCO utilisations and indicates that it could be used as an asphalt rejuvenator that is both environmentally friendly and able to create high quality pavements.